Modeling choice of breeding services by smallholder dairy farmers in the Kenyan highlands. - Omony, J. (University of Nairobi, 2004)
A socio-economic survey was conducted in three districts;- Kirinyaga, Rachuonyo and Nakuru within the Kenya highlands in February to May 2004. The objective of the study was to assess demand for breeding services of smallholder dairy farmers. The major constraints experienced by the respondents in this study were lack of adequate improved breeding facilities and the relatively high prices charged by the inseminators for the local and imported semen. Other constraints included the long distance to inseminators and service centres. Cost and availability of AI services were rated as major constraints by 51% and 47% respectively of the respondents. If resource-poor households are to continue to benefit from dairy production, a better understanding is required of the population, herd structures and dynamics in the smallholder sub-sector including the breeding (reproductive management and replacement) strategies of the smallholders. The majority of the smallholder dairy farms has few hectares and rear a small herd of less than ten heads of cattle. This calls for the need to intensify the farming system so as to obtain maximum yields. Before liberalization, the government of Kenya was solely involved in the management of Artificial Insemination (AI) services. However operational inefficiencies and budgetary constraints undermined service provision and AI services began to decline. In 1992, the sector was liberalized and the private sector stepped in to boost the AI service provision. However, with continued government involvement, tne - private sectors' performance has shown a downward trend in the past decade that needs to be studied to suggest policy recommendations. Investigations into what factors smallholder farmers put into consideration when choosing breeding bulls were also carried out. As ~ould be expected, farmers preferred bulls that are of high genetic quality (superior breeds), large body size and above all that are available. It was also found out that, faced with the problem of low quality bulls for breeding farmers had no room for choice and still used the low quality bulls that were easy to access